Electrochemiluminescence of Carbon Dots and Nitrogen-Doped Carbon Dots from a Microwave-Assisted Method - Nurul Izzati Akmal Mohd Azman; Muhammad Amirul Afiq Abdul Halim; Nur Syakimah Ismail; Nur Hamidah Abdul Halim; Nurjuliana Juhari; Norhayati Sabani; Siti Aisyah Shamsudin; Eiichi Tamiya, (International Journal of Nanoelectronics and Materials (IJNeaM), 2024)
This research focuses on the use of carbon dots (CDs) and nitrogen-doped carbon dots (NCDs) synthesized using a microwave-assisted method as electrochemiluminescence (ECL) luminophores. CDs have been synthesized using citric acid, while various concentrations of nitrogen-doped CDs have been successfully obtained by varying the amount of urea from 1 to 3 g with citric acid to produce NCD1, NCD,2 and NCD3. The ECL mechanism of CDs and NCDs on screen-printed electrodes has been studied using cyclic voltammetry (CV). ECL emission from as-prepared CDs and NCDs was observed in PBS with potassium persulfate (K2S2O8) as a co-reactant. The addition of potassium chloride (KCl) as a supporting electrolyte displays fast electroreduction of CDs and K2S2O8 to expedite the generation of CDs and peroxydisulfate radicals that simultaneously increase ECL intensity. Furthermore, as the concentration of nitrogen-doped CDs increases, so does the intensity of the ECL. NCD3 shows the highest ECL intensity by an increment of 86.4% in comparison to CDs in PBS with the addition of K2S2O8 and KCl. Finally, optimization of ECL measurement was carried out in terms of CV potential range, concentration of luminophore, supporting electrolyte, and co-reactant using NCD3 luminophore. The CV potential range at 0 to -2 V shows 50 mV of early CV reverse onset potential that resulted in an increase of 52.9% ECL intensity. Meanwhile, 30x dilution of NCD3, 0.1 M of supporting electrolyte KCl, and 0.1 M of co-reactant K2S2O8 show the optimum value to obtain high ECL intensity.